Anti-Corporate Anger as a Form of Care-Based Moral Agency - Simola, Sheldene (Journal of business ethics, 2010)
Conventional management strategies for anti-corporate anger involve its negative construal as an inappropriate irrationality in need of containment. An alternative account is offered in which such anger comprises a healthy and health-sustaining component of care-based moral agency directed not only toward the affiliative advancement of connection among community members, but also toward the (political) resistance to violation, injustice, and carelessness through which disconnection from responsive community relationships occurs. The role of anger in care-based moral agency is demonstrated through discussion of the classic case of environmental and human health crisis at Love Canal, New York.